Peran Leader Travel Umrah Zafir Tour Dalam Pengembangan Kualitas Pelayanan Terhadap Pelanggan - Anwar Ibrahim; Candra Darmawan (Social Science and Contemporary Issues Journal, 2023)
ABSTRACT: This research is entitled The role of the Umrah Zafir tour travel leader in developing service quality for customers. The problem raised in this research is the role of the Umrah Zafir Tour Travel leader in developing the quality of service to customers and what are the supporting and inhibiting factors in service to customers. The aim of this research is to determine the role of the leader, as well as the impact of supporting and inhibiting factors in service to customers on the Umrah Zafir Tour. This research uses a qualitative approach, with data sources namely primary and secondary data. The data collection techniques used were interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The conclusions of this research are: 1. The role of the leader in providing services to the congregation is very necessary so that the service continues to run smoothly, and the candidates and registered congregation feel safe and comfortable. The role of a leader is really needed to ensure Zafir travel management is carried out well. Leaders also set an example for employees to apply to consumers so that consumers are confident in choosing Zafir travel to accompany the Umrah pilgrimage. 2. Supporting factors in the service, one of which is a speaker/loudspeaker to call the congregation who are separated from the group so they can immediately reach the gathering point, the loudspeaker is very helpful for congregations who are elderly, we prioritize the elderly because the elderly are easy and very vulnerable so they must be take note. Inhibiting factors in service are pilgrims who are left behind or lost, pilgrims who are sick due to differences in weather between Indonesia and Arabia, so pilgrims are very vulnerable to illness, pilgrims who do not understand the technology that has developed.